2014
DOI: 10.4149/gpb_2013061
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Ghrelin Response to Chronic Immobilization Stress in Rats: Possible Role of Estrogen

Abstract: Abstract. Ghrelin is a peptidergic hormone known to be one of the main hormones involved in the regulation of energy balance. Here we evaluated ghrelin response to stress in rats after ovariectomy and during estradiol benzoate (EB) therapy and compared results of males and females, to know whether ghrelin is involved in disordered eating behaviors in response to stress, and for understanding differences between males and females in food intake and weight gain especially during stress. 96 adult rats were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The authors postulated that menopausal status could potentially affect bariatric surgery outcome in a procedure-dependent manner. Translational research using animal models suggests that absence of oestrogen alters ghrelin responses [ 35 ], which could potentially explain the altered effects of SG in women who are over the age of 50. Interestingly, in men, weight outcomes with SG improved relative to RYGBP with increasing age, suggesting that a sex-specific factor is important for SG response.…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated that menopausal status could potentially affect bariatric surgery outcome in a procedure-dependent manner. Translational research using animal models suggests that absence of oestrogen alters ghrelin responses [ 35 ], which could potentially explain the altered effects of SG in women who are over the age of 50. Interestingly, in men, weight outcomes with SG improved relative to RYGBP with increasing age, suggesting that a sex-specific factor is important for SG response.…”
Section: Discussionmentioning
confidence: 99%
“…Early life stress induced by limited access to bedding and nesting material for a week led to attenuated weight gain during stress exposure in male and female pups, which was compensated by an increased weight gain after termination of the stress exposure (Yam et al, 2017). As an exception, only one study found increased food intake and body weight gain during immobilization stress over a period of three weeks, which was more pronounced in male than female rats (Elbassuoni, 2014).…”
Section: Effects Of Stress On Food Intake and Body Weight In Rodents mentioning
confidence: 99%
“…Similarly, chronic mild unpredictable stress (CUMS) protocols were shown to induce elevated total serum ghrelin levels in rats (Lopez Lopez et al, 2018) and plasma AG levels in mice (Patterson et al, 2010;Huang et al, 2017). Also chronic immobilization stress increased ghrelin or AG levels in rats (Elbassuoni, 2014;Meyer et al, 2014). A recent study showed that elevated plasma AG levels following chronic immobilization stress in adolescent rats persisted up to four months after stress exposure (Yousufzai et al, 2018).…”
Section: Effects Of Stress On Plasma Ghrelin Levels In Rodentsmentioning
confidence: 99%
“…We found that lack of gonadal steroids in ORX males did not have any effect on ghrelin levels, whereas serum ghrelin levels in OVX females were drastically reduced and indistinguishable from ghrelin levels found in males. While a previous study indicated a similar effect of gonadectomy ( 35 ), also the opposite has been reported ( 21 , 36 ). Matsubara et al.…”
Section: Discussionmentioning
confidence: 64%